ANALISIS BIBLIOMETRIK : PLAYTHERAPY PERMAINAN TRADISIONAL UNTUK MENANGGULANGI DAMPAK BURUK GLOBALISASI - Mirza Ghulam Abdullah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This research aim to reveal the trends of playtherapy traditional game research. Bilbliometric analysis were used to find the trend of playtherapy traditional game research. The data is collected using Publish or Perish with Google Scholar as the source. Using playtherapy and traditional game as the keywords, there are 966 paper from 2019-2024 time period in google scholar. Then the data is processed with the help of VOSviewer. The output of this process came out as 3 maps, 1) Network visualization, 2) Overlay visualization and 3) Density visualization. The result of this analysis found that there is no development of playtherapy traditional game published paper after 2021. The improvement of social skills is the most discussed topic and student social skills came as the second discussed topic. Through this research it is hoped that many parties will be helped and make this findings as their material of further research on related discussions.